Michael Addition of N-Heteroaromatics to Vinylphosphonates and Synthesis of Phosphoryl Pyrrolizones by Cyclization of Michael Adducts - Tasgin, Dilek Isik; Unaleroglu, Canan (Synthesis, 2013)
Novel phosphonate compounds were synthesized via Michael addition of N-heteroaromatic compounds to aryl- and alkyl-substituted vinylphosphonates using scandium triflate as the catalyst. Intramolecular cyclization reaction of the Michael adducts obtained gives novel (dimethoxyphosphoryl)pyrrolizin-3-ones in high yields as a single diastereomer.
Keywords: phosphonates; pyrrolizinones; Michael addition; metal triflates; heteroaromatic compounds